Formal examiner training reflects the increased expertise required of RACS examiners. Issue 6 (3rd May 2013) - Beasley, Spencer W.; Lander, Richard; Brooks, Andrew J.; Hardware, Narelle
Abstract The Fellowship Examination is the final summative assessment before the Surgical Education and Training trainees are awarded Fellowship of the Royal Australasian College of Surgeons. Conducted in nine specialties, it is aligned with the curriculum of each specialty training programme. The Fellowship Examination focuses on specific surgical competencies; in particular, the clinical application of knowledge, operative decision making and professional judgement. As a true 'exit' examination, it has to be conducted at the correct cognitive level for surgeons about to enter practice without direct supervision. This requires examiners to have specific skills and expertise for which training is required. This paper outlines the process of training undertaken by newly appointed examiners, and describes some of the areas of knowledge that they have to master before examining at the consistently high level that is now expected.